Cyclocarya paliurus Reprograms the Flavonoid Biosynthesis Pathway Against Colletotrichum fructicola - Zheng, Xiang-Rong; Zhang, Mao-Jiao; Qiao, Yu-Hang; Li, Ran; Alkan, Noam; Chen, Jie-Yin; Chen, Feng-Mao (Frontiers in Plant Science, 2022)
Cyclocarya paliurus is an endemic Chinese tree species with considerable medicinal, timber, and horticultural value. The anthracnose disease of C. paliurus is caused by the fungal pathogen Colletotrichum fructicola, which resulting in great losses in yield and quality. Here, resistance evaluation of six cultivars of C. paliurus exhibited varying degrees of resistance to C. fructicola infection, where Wufeng was the most resistant and Jianggangshan was the most susceptive. Physiological measurements and histochemical staining assays showed that the Wufeng cultivar exhibits intense reactive oxygen species accumulation and defense capabilities. A multiomics approach using RNA sequencing and metabolome analyses showed that resistance in C. paliurus (Wufeng) is related to early induction of reprogramming of the flavonoid biosynthesis pathway. In vitro antifungal assays revealed that the flavonoid extracts from resistant cultivars strongerly inhibited C. fructicola hyphal growth than susceptible cultivar. Relative gene expression analysis further demonstrated the pivotal antifungal role of C. paliurus flavonoids in targeting Colletotrichum appressorium formation. Together, these results represent a novel resistance mechanism of C. paliurus against anthracnose through the reprogramming of flavonoid, which will lay a foundation for breeding anthracnose-resistant varieties and for the application of flavonoid extraction of C. paliurus as a natural antifungal treatment.